Water availability analysis of multiple source groundwater supply systems in water stressed urban centers: case of Lodwar municipality, Kenya - Maxwell, CO; Dulo, S; Olago, DO; Odira, PMA (Hilaris, 2020)
Ensuring water security to urban population in fragile environments through interlinked systems of groundwater abstraction, storage and distribution of sufficient quantity is challenging especially to urban utilities situated in arid and semi arid regions. The purpose of this research was to evaluate water delivery challenges for water utilities in fragile environment in Kenya. A systematic analysis of availability from each supply sub-components from source to consumer was carried out through water audit and network analysis by employing water flow measurement equipments and through pump performance analysis and by employing continuity equation and Bernoulli’s principle to sections of the network. Results showed that water availability within a utility in such environments is contributed by seasonal variations between wet and dry affecting quantity at source, optimal design of supply infrastructure in this case better matching of solar power with the pump, using standard pipes and on optimal operational strategies employed to reduce losses within the network. Based on these findings, we conclude that with clear understanding of each subcomponent’s contributions to entire water supply system and optimizing their design and operations, more people will be made water secure in all seasons in the fragile environments.